200k views
3 votes
What is the product of( 2x^2+4x-2) and (3x+6)

User Olatunji
by
6.0k points

2 Answers

5 votes
hey user!!

your answer is here...

given :- ( 2x² + 4x - 2 ) × ( 3x + 6 )

= 3x ( 2x² + 4x - 2 ) + 6 ( 2x² + 4x - 2 )

= 6x³ + 12x² - 6x + 12x² + 24x - 12

= 6x³ + 24x² + 18x - 12

cheers!!
User George Profenza
by
4.5k points
0 votes
Hi friend
--------------
Your answer
---------------------

(2x² + 4x - 2) × (3x + 6)

= 2x²(3x + 6) + 4x(3x + 6) - 2(3x + 6). [Using distributive property of multiplication]

= 6x³ + 12x² + 12x² + 24x - 6x - 12

= 6x³ + 24x² + 18x - 12

HOPE IT HELPS
User Mo Moosa
by
5.1k points